2009
DOI: 10.1111/j.1538-7836.2009.03275.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk profile and morphological pattern of venous thromboembolism after prostate cancer surgery

Abstract: To cite this article: Beyer J, Wessela S, Hakenberg OW, Kuhlisch E, Halbritter K, Froehner M, Wirth MP, Schellong SM. Incidence, risk profile and morphological pattern of venous thromboembolism after prostate cancer surgery. J Thromb Haemost 2009; 7: 597-604.Summary. Background: Venous thromboembolism (VTE) is the most common non-surgical complication after major pelvic surgery. Little is known about the risk factors or the time of development of postoperative venous thrombosis. Methods: A cohort of 523 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 45 publications
6
47
0
4
Order By: Relevance
“…Nonetheless, previous surgeries and disease progression are strongly associated with an increased risk of TED and should be accounted for when assessing the impact of ADT on TED [1][2][3][4][5][6][7][8][9][10]. In our previous study, we observed an increased risk of TED in men with PCa on ADT compared with the general Swedish male population, although a number of health and lifestyle factors could not be accounted for [2].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nonetheless, previous surgeries and disease progression are strongly associated with an increased risk of TED and should be accounted for when assessing the impact of ADT on TED [1][2][3][4][5][6][7][8][9][10]. In our previous study, we observed an increased risk of TED in men with PCa on ADT compared with the general Swedish male population, although a number of health and lifestyle factors could not be accounted for [2].…”
Section: Discussionmentioning
confidence: 97%
“…Surgery and disease severity are known to increase the risk of thromboembolic disease (TED) in men with prostate cancer (PCa) [1][2][3][4][5][6][7][8][9]. The risk of TED is further enhanced in men with PCa treated with androgen deprivation therapy (ADT) [1,2,10,11]; however, it is unknown to what extent ADT influences the risk of TED when accounting for previous surgeries and disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Other evidence to support the NICE recommendations but not considered by NICE include work by Beyer et al [14] who published a study that investigated the incidence of VTE after RP. The authors reported that 16.8% of patients had a DVT after RP, of which 5.8% had a PE.…”
Section: Discussionmentioning
confidence: 99%
“…Hammond et al analyzed 20,000 extensive oncological surgeries, including urological oncological surgery and found that symptomatic VTE occurred in 1.8% of patients after prostatectomy [201]. In cases, where no prophylaxis was applied and thromboembolic complications were assessed by the means of imaging methods after prostatectomy, the risk seems to be significantly higher (16.8-32%), which results from high percentage of asymptomatic deep venous thrombosis cases [203][204].…”
Section: Venous Thromboembolism Prophylaxis In Cancer Patientsmentioning
confidence: 99%